2023
DOI: 10.3390/jcm12031020
|View full text |Cite
|
Sign up to set email alerts
|

Heart Failure Pharmacological Management: Gaps and Current Perspectives

Abstract: Proper therapeutic management of patients with heart failure (HF) is a major challenge for cardiologists. Current guidelines indicate to start therapy with angiotensin converting enzyme inhibitors/ angiotensin receptor neprilysin inhibitors (ACEi/ARNI), beta blockers (BB), mineralocorticoid receptor antagonists and sodium glucose cotransporter 2 inhibitors (SGLT2i) to reduce the risk of death and hospitalization due to HF. However, certain aspects still need to be defined. Current guidelines propose therapeuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 77 publications
0
13
0
Order By: Relevance
“…The complexity of the HF syndrome requires a global, multiparametric, and objective approach to patients, going beyond the cardiocentric view based on LVEF and HF symptoms, addressing the pathophysiological mechanisms underlying heart abnormalities 25,26,30,31 . We propose the HLM score as a new, multivariable, user‐friendly, and pragmatic classification model in the HF population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complexity of the HF syndrome requires a global, multiparametric, and objective approach to patients, going beyond the cardiocentric view based on LVEF and HF symptoms, addressing the pathophysiological mechanisms underlying heart abnormalities 25,26,30,31 . We propose the HLM score as a new, multivariable, user‐friendly, and pragmatic classification model in the HF population.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of the HF syndrome requires a global, multiparametric, and objective approach to patients, going beyond the cardiocentric view based on LVEF and HF symptoms, addressing the pathophysiological mechanisms underlying heart abnormalities. 25 , 26 , 30 , 31 We propose the HLM score as a new, multivariable, user‐friendly, and pragmatic classification model in the HF population. Although developed in a relatively small study population, HLM demonstrated the best overall accuracy in predicting the composite of all‐cause death and rehospitalization due to HF, at 12 months, compared with currently used prognostic models, representing a promising tool to guide HF staging and management.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the pathophysiology and the treatment available for HF with mildly reduced ejection fraction (HFmrEF) and HF with preserved ejection fraction (HFpEF) patients remain unclear. In these populations, TM may play an additive role, being a tool to prevent hospitalizations, thus improving the prognosis [ 47 , 48 ]. A subanalysis of the recent ICOR study aimed to evaluate the efficacy of TM in these patients, in terms of risk of non-fatal acute HF and risk of hospitalization after 6 months of follow-up [ 49 ].…”
Section: Telemedicine and Heart Failurementioning
confidence: 99%
“…However, LVEF has high variability and low repeatability. In various guidelines, the critical values of LVEF in different HF subtypes are different, and there is still a lack of definition of the normal range [ 7 , 8 ]. According to both European and American guidelines, HF is divided into three subtypes: heart failure with preserved ejection fraction (HFpEF, LVEF ≥ 50%), heart failure with mid-range ejection fraction (HFmrEF, LVEF ≥ 40 and < 50%), and heart failure with reduced ejection fraction (HFrEF, LVEF < 40%) [ 6 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%